2005
DOI: 10.1182/blood.v106.11.346.346
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety and Efficacy of Two Novel Immunotoxins Consisting of Ranpirnase (Rap) Fused to an Internalizing Anti-CD74 Humanized IgG4 Antibody in Human Non-Hodgkin’s Lymphoma Xenografts.

Abstract: Rap, an amphibian ribonuclease, is a single-chain protein of 104 amino acids that kills cells by degrading t-RNA upon internalization. CD74 is a rapidly internalizing type-II transmembrane chaperone molecule associated with HLA-DR, and has high expression on hematological malignancies including B-cell non-Hodgkin’s lymphoma (NHL) and multiple myeloma (MM). We have constructed and evaluated two novel immunotoxins, 2L-Rap-hLL1-γ 4P and 2L-Rap(N69Q)-hLL1-γ 4P, each composed of two Rap molecules fused to hLL1, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 22 , 23 Preclinical studies have shown that not only can the antibody induce apoptosis when bound to its target, but also that the rapid internalization and recycling of CD74 makes it possible to conjugate chemotherapeutics, radioisotopes and other toxins to the drug to make targeted, efficacious killing a possibility. 24 30 However, clinical trials using milatuzumab in MM have yet to demonstrate significant activity. 31 …”
Section: Monoclonal Antibodies In Multiple Myelomamentioning
confidence: 99%
“… 22 , 23 Preclinical studies have shown that not only can the antibody induce apoptosis when bound to its target, but also that the rapid internalization and recycling of CD74 makes it possible to conjugate chemotherapeutics, radioisotopes and other toxins to the drug to make targeted, efficacious killing a possibility. 24 30 However, clinical trials using milatuzumab in MM have yet to demonstrate significant activity. 31 …”
Section: Monoclonal Antibodies In Multiple Myelomamentioning
confidence: 99%